SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Validation of a molecular sex marker in three sturgeons from eastern North America - Nicholas M. Sard; Brian R. Kreiser; Richard M. Pendleton; Barbara A. Lubinski; Robin L. Johnson; Dewayne A. Fox; Joel P Van Eenennaam; Jason E. Kahn; Chris Hager; Amanda L. Higgs; David C. Kazyak (Conservation Genetics Resources, 2024)

It’s about time: A synthesis of changing phenology in the Gulf of Maine ecosystem - Michelle D. Staudinger; Katherine E. Mills; Karen Stamieszkin; Nicholas R. Record; Christine A. Hudak; Andrew Allyn; Antony Diamond; Kevin D. Friedland; Walt Golet; Meghan Elisabeth Henderson; Christina M. Hernandez; Thomas G. Huntington; et al. (Fisheries Oceanography, 2019)
The timing of recurring biological and seasonal environmental events is changing on a global scale relative to temperature and other climate drivers. This study considers the Gulf of Maine ecosystem, a region of high social and ecological importance in the Northwest Atlantic Ocean and synthesizes current knowledge of (a) key seasonal processes, patterns, and events; (b) direct evidence for shifts in timing; (c) implications of phenological responses for linked ecological‐human systems; and (d) potential phenology‐focused adaptation strategies and actions. Twenty studies demonstrated shifts in timing of regional marine organisms and seasonal environmental events. The most common response was earlier timing, observed in spring onset, spring and winter hydrology, zooplankton abundance, occurrence of several larval fishes, and diadromous fish migrations. Later timing was documented for fall onset, reproduction and fledging in Atlantic puffins, spring and fall phytoplankton blooms, and occurrence of additional larval fishes. Changes in event duration generally increased and were detected in zooplankton peak abundance, early life history periods of macro‐invertebrates, and lobster fishery landings. Reduced duration was observed in winter–spring ice‐affected stream flows. Two studies projected phenological changes, both finding diapause duration would decrease in zooplankton under future climate scenarios. Phenological responses were species‐specific and varied depending on the environmental driver, spatial, and temporal scales evaluated. Overall, a wide range of baseline phenology and relevant modeling studies exist, yet surprisingly few document long‐term shifts. Results reveal a need for increased emphasis on phenological shifts in the Gulf of Maine and identify opportunities for future research and consideration of phenological changes in adaptation efforts.

Competition among river planktivores: are native planktivores still fewer and skinnier in response to the Silver Carp invasion? - Richard M. Pendleton; Christopher Schwinghamer; Levi E. Solomon; Andrew F. Casper (Environmental Biology of Fishes, 2017)

Long-term changes in fish community structure in relation to the establishment of Asian carps in a large floodplain river - Levi E. Solomon; Richard M. Pendleton; John H. Chick; Andrew F. Casper (Biological Invasions, 2016)

Trophic downgrading results in complex ecosystem dynamics in experimental tropical floodplain food webs - Richard M. Pendleton; David J. Hoeinghaus; Luiz C. Gomes; Angelo A. Agostinho (Hydrobiologia, 2015)

Erratum to: The impact of climate change on California’s ecosystem services - M. Rebecca Shaw; Linwood Pendleton; D. Richard Cameron; Belinda Morris; Dominique Bachelet; Kirk Klausmeyer; Jason MacKenzie; David R. Conklin; Gregory N. Bratman; James Lenihan; Erik Haunreiter; Christopher Daly; et al. (Climatic Change, 2012)

The impact of climate change on California’s ecosystem services - M. Rebecca Shaw; Linwood Pendleton; D. Richard Cameron; Belinda Morris; Dominique Bachelet; Kirk Klausmeyer; Jason MacKenzie; David R. Conklin; Gregrory N. Bratman; James Lenihan; Erik Haunreiter; Christopher Daly; et al. (Climatic Change, 2011)